Capturing and documenting creative processes in contemporary dance - Ribeiro, C.; dos Anjos, K. R.; Fernandes, C. . (Proceedings of the 4th International Conference on Movement Computing, 2017)
The performing arts, and dance in particular, have been considered as intangible cultural heritage by UNESCO since 2003. This acknowledgement reflects the importance of preserving the knowledge generated within this art form for future generations. Nevertheless, what and how this sensible material should be preserved is still lacking clear methodological approaches. When considering creative processes, this seems an even more daunting task, as it goes beyond simply documenting the final product of a creation. Recent advancements in technology has allowed to consider other approaches of capturing data apart from video or photography, which are mostly static and have a single viewpoint. In this paper we describe how 3D data capture and point cloud visualization techniques have been used to capture and document João Fiadeiro's choreographic and compositional processes. Together with Fiadeiro we have identified a sub-set of core concepts of his method which have then been used to conduct two improvisation sessions involving Fiadeiro's dancers and himself. Those concepts have been used as the basis for the development of new visualization techniques that better illustrate, in an interactive system, the complexity of Fiadeiro's creative process.